THE IMPORTANCE OF THE HUMAN RIGHTS MOVEMENT IN THE UNITED STATES: FROM ABOLITION TO THE CIVIL RIGHTS MOVEMENT (1865-1968) - Santi Dame Mawarni; Eko Ribawati; Tubagus Noeriman Achmad Sumantri (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
This research aims to understand the importance of the human rights movement in the United States from the abolition period to the civil rights movement. Descriptive qualitative methods were used to gain an in-depth understanding of the impact and social changes produced by this movement. The research results show that the human rights movement has had a significant impact on the fight for equality and eliminating racial discrimination in the United States. During the abolition period, this movement aimed to abolish the existing system of slavery, and through peaceful actions, demonstrations, and campaigns, this movement succeeded in raising public awareness of the importance of human rights. During the civil rights movement, the movement became broader and aimed to fight for civil, political, and social rights for all citizens of the United States regardless of race, religion, or ethnic background. Through this movement, significant legislative and court decisions have been produced, such as the Brown v. Browns decision—Board of Education in 1954, which overturned racial segregation in schools. The importance of the human rights movement is also seen in the social and cultural changes it produced. Americans are becoming more aware of the importance of respecting human rights and upholding the values of equality. The results of this research emphasize that this movement not only influenced the United States at that time but also had a long-term impact in promoting equality and human rights worldwide. Through this research, we can better understand the importance of the civil rights movement in the United States and its contribution to profound social change. This research also shows its relevance in the current context, where human rights issues are still a significant concern in global society.